O nascimento da nação: Estado, modernização nacional e relações étnico-raciais entre o Império e o início da República - Ronaldo Sales (Ciências Sociais Unisinos)
The aim of this article is to present the relation between ethnic-racial relationships as power relationships and the constitution of a model of national sovereignty as ethnic-racial domination. Having analyzed this relation, it is possible to understand that contemporary racism and authoritarianism are not pre-moderns or colonial heritage, but they are outcomes of the modernization process of Brazilian republican institutions.